Plan de negocios para empresa distribuidora de productos de aseo general en la ciudad de Palmira, Valle del Cauca (2021)
The proposal of this business plan seeks to provide small distributors and neighborhood stores mainly in the city of Palmira Valle del Cauca, distribution of cleaning products and general disinfection, focusing on value propositions such as service, agility and quality of the product.